The Effect of Guided Inquiry Model Assisted by Animation Video on Students’ Concept Mastering of Wave Materials - Wildani, Arin; Budiyono, Agus; Triastutik, Milisa; Junaidi, Junaidi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to determine the effect of guided inquiry model assisted by animated videos on students’ mastery of physics concepts. This research is an experimental research. The method used in this study is a quasi-experimental with pretest posttest control group design. The population in this study were all students of class VII SMPI Terpadu Miftahul Ulum Tambelangan. The sample in this study is class VIII A as the experimental class and class VIIID as the control class, each class consists of 32 students. Determination of the sample using simple random sampling technique. The instrument in this study is a concept mastery test with 10 questions on wave material, which have been declared valid and reliable. Data analysis was done by t test with N-Gain test. Based on the results of the t-test analysis, the results of t-count (7.932) > t-table (1.98), and based on the N-gain test obtained a value of 0.85 where the increase is included in the high category. From these results it can be concluded that the learning process with the guided inquiry model assisted by animated videos has a significant effect on students’ mastery of concepts.